“The Work to Wonder at — Perhaps a Stowe”: The History of the Model Landscape Park and Its Role in Garden Art of the Enlightenment - Sokolov, Boris M. (Actual Problems of Theory and History of Art, 2016)
The subject matter of the paper is the history of creation and changing descriptions of the Stowe estate (Buckinghamshire, England), a landmark of the English landscape style. The present design of this park is a summation of several constructing periods; each of them enriched the program and scenes. The Stowe estate happened to be the first English garden to receive its own guide book (1744); its descriptions reveal the changing interpretation of the landscape. The influence of Stowe (Mereville, Woerlitz, Tsarskoye Selo) was not limited to copying of its monuments, since the park was also an example of metaphorical and emotionally charged garden scene. The current research follows the stages of the park development and brings to the attention of the Russian audience some important texts by Alexander Pope, Thomas Richardson and Thomas Whately. The aim of the presentation is to show the gradual sublimation of the image of Stowe, for at the beginning (1720s–1740s) the estate was mostly appreciated as a collection of monuments and inscriptions displayed in the beautiful setting, though at the mature stage of English garden theory (second half of the 18th century), as exemplified by Whately’s Observations, Stowe was praised as an ideal landscape, a continuity of nice scenes rich in associations, inspired by monuments, but unfolding further towards the realms of fantasy and meditation.